ANALYSIS OF FARMERS' SATISFACTION TOWARDS ABSOLUT 69 BIRD'S CHILI SEEDS IN THE SPECIAL REGION OF YOGYAKARTA USING THE CUSTOMER SATISFACTION INDEX (CSI) METHOD - Roy Pulan; Ananti Yekti; Agus Wartapa (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Superior seeds play an important role in increasing cayenne pepper productivity; however, studies specifically examining farmer satisfaction with particular seed products remain limited. This study aimed to analyze the satisfaction level of farmers using Absolut 69 cayenne pepper seeds produced by PT. Mitra Merdeka Tani in the Special Region of Yogyakarta (DIY) using the Customer Satisfaction Index (CSI) method. The research was conducted from November 2025 to April 2026 in Sleman, Bantul, and Kulon Progo Regencies. A total of 100 farmers were selected through purposive sampling, with the criterion that they had used Absolut 69 seeds for at least two consecutive planting seasons. Data were collected using a structured questionnaire with a 1–4 Likert scale covering 21 satisfaction attributes grouped into five dimensions. The results showed a CSI value of 80.12%, indicating that farmers were highly satisfied with the product. The attribute with the highest importance level (MIS) was fruit quality, including color, size, and shape (3.29), while the lowest importance level was found in the benefits of promotional activities (3.04). In terms of performance (MSS), ease of access to seed sellers or distributors achieved the highest score (3.41), reflecting good distribution accessibility for farmers. Conversely, seed stock availability during the planting season recorded the lowest performance score (3.06), indicating supply constraints during periods of high demand. Overall, farmers expressed a very high level of satisfaction with Absolut 69 seeds; however, improvements in distribution management and stock availability should be prioritized to sustain farmer satisfaction in the long term. Keywords: Absolut 69, cayenne pepper seeds, Customer Satisfaction Index, farmer satisfaction, seed products